Pengaruh Praktik Kerja Industri, Informasi Dunia Kerja Dan Motivasi Memasuki Dunia Kerja Terhadap Kesiapan Kerja Siswa - Susilo, Sri Muji; Ismiyati, Ismiyati (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of industrial work practices, information on the world of work and motivation to enter the world of work on student work readiness at SMK Bhakti Persada Kendal. The population in this study were all students of class XII Office Administration expertise program. The research sample consisted of 59 respondents who were taken from all students of class XII of the Office Administration expertise program of SMK Bhakti Persada Kendal. Data were collected by means of a questionnaire and analyzed by using multiple linear regression. The results of this study are (1) there is a partially positive effect of industrial work practices on job readiness of 18.49%, (2) there is a partial positive effect of information on the world of work on work readiness by 17.30%, (3) there is an effect Partially positive motivation to enter the world of work on work readiness is 14.66%, (4) there is a positive and significant effect simultaneously between the variables of industrial work practices, information on the world of work, and entering the world of work on student work readiness by 76.4%.